Kemampuan Penyesuaian Diri Pengaruhi Prestasi Akademik Mahasiswa - Nadiyah Nadiyah; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Lembaga Pengembangan Kinerja Dosen, 2023)
Study this own objective for reveal influence Ability Personal Adjustment (X1), Thinking patterns (X2), Motivation Learning (X3), and Independence Learn (Y) as intervening variable against Academic Achievement (Z). Study This designed with approach quantitative To use analyze connection variable free to variable bound or connection causal. Analysis model pattern connection between variable use analysis path (path analysis). Population in study This is Students of the Administrative Education Study Program The offices of the Class of 2020 and 2021, Faculty of Economics, Jakarta State University, were 174 respondents. Taking samples used technique Saturated Sampling and obtained maximum 174 respondents. For explain connection in a way direct between X1, X2 and X3, and Y against Z with analysis regression double as well as Outer Model use calculation of Convergent Reliability, Discriminant Validity, Composite Reliability, Cronbach's Alpha, and Inner Model with calculation of T statistics, R-square, f-square, and VIF with the help of SmartPLS (Partial Least Square) software version 4.0.9.3. Conclusion of study this is (1) ability adjustment self-influential to independence learn, (2) pattern think influential to independence learning, (3) motivation Study influential to independence learning, (4) independence Study influential to performance academic students, (5) ability adjustment self No influential to performance academic students, (6) motivation study influential to prestation academic students, (7) ability adjustment self with independence Study no influential to performance academic, (8) pattern think with independence Study influential to performance academic, and (9) motivation Study with independence Study influential to performance academic.